A most unsuitable match - Whitson, Stephanie Grace (Bethany House, 2011)
Fannie is traveling west to uncover the truth behind a family secret. Samuel is on a mission to atone for past failures that still haunt him. Their meeting aboard a steamboat headed to Montana sparks an unlikely attraction. Will the end of their journey bring the end of their relationship-- or is it just the beginning?